Diagnostic Reasoning Assessment Toolkit: Guided Reflection and Standardized Cases for At-Risk Final-Year Medical Students - Cory Pitre (Association of American Medical Colleges, 2016)
Abstract Introduction A failing diagnostic reasoning performance may represent student deficiency in a number of potential areas. However, many standard clinical skills assessments do not offer detailed assessments of diagnostic reasoning ability. This toolkit was designed to identify specific learner deficiencies with respect to diagnostic reasoning by focusing on individual student remedial work and by standardizing faculty evaluation. Methods Educational objectives were derived from institutional patient care competency learning objectives at the Indiana University School of Medicine. Review of existing clinical skills remediation literature yielded a design that combined two learning methods: guided reflection and standardized patient cases. Results Over the 2014-2015 academic year, 12 final-year medical students used this resource to help develop an individual remedial learning plan prior to retaking a failed standardized assessment. Students were generally satisfied with the combined guided reflection and standardized case learning methods. Discussion Unique final-year medical student scheduling pressures, combined with a reporting time line for both institutional high-stakes OSCE remediation exams and the USMLE Step 2 Clinical Skills exam, incentivized failing students to schedule a retest on a short time line, often leaving little time for critical preparation. This resource offered an opportunity to efficiently spend limited preparation time to individualize exam preparation using a variety of faculty facilitators. The simplistic design was readily deployable to multiple faculty remediation mentors. Our institution can now provide a standardized diagnostic reasoning remedial evaluation using numerous clinical faculty based at any of our nine campuses.